Data repository for teacher education scoping study. - Willis, Sue; Preston, Barbara (Australian Learning and Teaching Council (ALTC), 2009)
This is a scoping study carried out by The Australian Council of Deans of Education (ACDE) through Monash University to investigate the need and support for, and feasibility and specifications of, a national data repository for teacher education (DRTE) with systematically managed, accessible and usable data concerned with teacher education and related areas. Chapters cover aspects of the proposed DRTE such as: context; location, management and funding; structure; data principles and standards; content; and recommendations.